Effect of endorphin massage on breast milk production in postpartum mothers at Pratama Hadijah Maternity Clinic - Nasution, Yulia Fatma; R, Maimunah; Lubis, Desi Handayani; Sitorus, Nopita Yanti; Fauziah, Yaumil; Nasution, Annisa Namirah (Science Midwifery, 2025)
Endorphins play a role in creating a sense of comfort and pleasure, which can help reduce anxiety in mothers. Back massage is done to stimulate the oxytocin reflex through somatic sensory stimulation of the afferent system. The purpose of this study was to determine the effect of endorphin massage on breast milk production in post partum mothers at Pratama Hadijah Maternity Clinic in 2025. This study used a quasi-experimental design with a quantitative approach. The research was conducted from February to April 2025 at Pratama Hadijah Maternity Clinic. The study population included all postpartum mothers who visited Pratama Hadijah Maternity Clinic from February to April 2025. The sample used was 54 people, obtained through purposive sampling technique, and the data were analyzed using the Mann Whitney test. The results showed that as many as 36 respondents (66,7%) experienced smooth milk production after being given endorphin massage, while 18 other respondents (33,3%) showed less smooth milk production. There is a significant relationship between endorphin massage and breast milk production in post partum mothers, with a Z value of - 3.178 with a p value of 0.001 <0.05. It was concluded that mothers who received endorphin massage showed smoother breast milk production than those who did not receive the treatment. It is recommended to the clinic to apply endorphin massage therapy which is proven to have an effect on breast milk production.